Does economic prosperity translate to regional youth employment?. (2nd July 2020) - Dayaram, Kantha; Rola Rubzen, Fay; Ahmad, Hasnat; Britten, Naomi
ABSTRACT: There is a consensus that the retention of youth in regional locations is fundamental to building sustainable regional communities; however, the lack of employment opportunities is a dominant cause of regional youth out-migration. It is plausible that economic prosperity arising from resource booms would create job opportunities and extend youth employment rates even in regional locations. We, therefore, analyse the Western Australian case of a decade-long mining boom (2004–2014) using secondary policy data and primary focus group interviews with youth from regional locations. We examine their employment experiences and the labour policy initiatives during a mining boom. A comparative analysis of secondary and primary data indicates the need for focussed regional inclusion initiatives. Our study suggests the need to implement localised youth employment policy interventions. The study highlights the policy implications particularly for future economic windfalls and international resource-rich regions seeking to broaden their regional development agendas and address overall unemployment.